Du double à la figure - genèse d’un personnage christique chez Dambudzo Marechera - Pierre Leroux (Continents manuscrits)
The Black Insider was published in 1992 as the first of three volumes dedicated to the posthumous works of Dambudzo Marechera. This text actually appears to be one of the versions rejected by editors prior to the acceptance of Black Sunlight (1980). Through the editing work and close analysis of genetic material consisting of several manuscripts including a poetic sequence due to conclude Black Sunlight, this article aims at finding a new angle to assess Marechera’s prose and his creative process. In order to get a better grasp on the elements at stake, we have decided to focus on the evolution of one character, Owen, who changes his name and status to become Nick in Black Sunlight.